Changes in Macular Microvascular Structure in Macular Edema Secondary to Branch Retinal Vein Occlusion Treated with Antivascular Endothelial Growth Factor for One Year - Shuang Song; Xiaobing Yu; Peng Zhang; Hong Dai (Journal of Ophthalmology, 2021)
Purpose. To observe the changes in macular microvascular structure and the correlation between anatomy and visual function in patients with macular edema secondary to branch retinal vein occlusion (BRVO) treated with antivascular endothelial growth factor for one year. Methods. This prospective study enrolled 39 patients (one eye per patient) who received intravitreal injections of ranibizumab for macular edema secondary to BRVO. All patients received a minimum of 3 initial monthly ranibizumab injections and criteria-driven pro re nata (PRN) dosing thereafter for visual acuity (VA) and central retinal thickness (CRT) stabilization. The follow-up period of this study was one year. The vascular density (VD) of the superficial retinal capillary plexus (SCP) and deep retinal capillary plexus (DCP), the foveal avascular zone (FAZ) area, the FAZ perimeter, the VD within a 300 μm wide ring surrounding the FAZ (FD-300), and the acircularity index (AI) were measured automatically by optical coherence tomography angiography (OCTA) at baseline, month 6, and month 12. Results. Compared with those before treatment, the VD of the SCP significantly decreased 6 months after treatment (P<0.05), while the area and perimeter of the FAZ increased significantly (P<0.01). After 12 months of treatment, the area and perimeter of the FAZ increased significantly (P<0.01). There was no significant difference in any parameters between 12 months and 6 months after treatment (P>0.05). The change in BCVA was negatively correlated with the VD of the SCP at 12 months (P=0.0447, r = −0.3233). There was a relationship between the DBP and AI, and CRT was related to VD of DCP at baseline (P=0.028, 0.0209; r = 0.383, −0.384). The PERIM and AI at 12 months were significantly associated with the recurrence of macular edema, and the changes in vascular density in the SCP and PERIM were significantly associated with the number of injections within 12 months (P<0.05). Conclusions. One year after ranibizumab treatment, the area and perimeter of the FAZ were enlarged, while the VD of the SCP and DCP remained stable, which indicated that ranibizumab treatment did not improve macular blood supply and macular ischemia in BRVO patients.